Antioxidant Potential of Red Palm-Pressed Mesocarp Olein - Mah, Siau Hui; Teh, Soek Sin; Loganathan, Radhika; Lau, Harrison Lik Nang; Teng, Kim Tiu (Journal of Oleo Science, 2021)
Oxidative stress occurs due to the imbalance amount of the free radicals and antioxidants in human body which often associated with numerous chronic diseases. The antioxidant properties of red palm-pressed mesocarp olein (PPMO) have not been widely studied. Therefore, antioxidant properties of PPMO relative to commercially available edible oils, namely red palm olein (RPO), palm olein (PO), extra virgin olive oil (OO) and extra virgin coconut oil (CNO) were studied. PPMO exhibited significant higher phytonutrients which more than 2-fold compared to the edible oils. Overall, antioxidant screening indicated that PPMO has significantly higher antioxidant activities than RPO, PO and CNO in term of DPPH, H2O2, NO scavenging and FIC; and significantly higher H2O2 and FIC than OO. The outcomes of this study reveal that PPMO is as good as commercially available edible oil, also a good source for food applications and dietary nutritional supplements. More importantly, the utilization of PPMO could mitigate oil palm waste problem and results in positive environmental impact.